PEMBERDAYAAN DAN PENINGKATAN KUALITAS ASET DESA DI BIDANG PENDIDIKAN DI MASA PANDEMI: Empowerment and Improvement of Village Asset Quality in Education During the Pandemic - Anas Ma'ruf Annizar; Rifqi Qonita Hulwana; Nurul Husein; Sinta Islahus Sa’adah (Ngarsa: Journal of Dedication Based on Local Wisdom, 2021)
Pakuniran village is one the villages in the maesan sub-district. In this village there are many potentials the have not been considered one of which is the low quality of knowledge resources, the level of education and the problem of economic factors. This study uses quantitative research methods with guildelines ABCD (asset based community development). Not only stop here, we also use analysis Eksploratori to form the variable in the village. Direction for improvement have also been mapped so that potential utilization between hamlets can participate and totality. Desa Pakuniran merupakan salah satu desa yang ada di kecamatan maesan. Di desa ini banyak po-tensi yang belum diperhatikan salah satunya adalah rendahnya kualitas sumber daya pengetahuan, tingkat pendidikan dan masalah faktor ekonomi. Penelitianini menggunakan metode penelitian kualitatifdengan model pengabdian ABCD (asset based community development). Tidak hanya ber-henti sampai disini, penulisjuga menggunakan analisis Eksploratori untuk membentuk variabel yang ada di desa tersebut. Arah perbaikan juga telah dipetakan agar pemanfaatan potensi antar dusun dapat berpartisipasi dan totalitas.